Scotland - Britton, Tamara L., 1963- (Edina, Minn. : Abdo Pub., 2003)
Provides an overview of the history, land, plants and animals, people, economy, cities, transportation, government, holidays and festivals, and sports and culture of Scotland, and includes a glossary, Web site resources for more information, a time line, and an index.
Sodan! -- Fast facts -- Timeline -- History -- The land -- Wild things -- The Scots -- Making money -- Important places -- Getting around -- The government -- Holidays & festivals -- Sports & culture -- Glossary -- Web sites.
Includes index.
Horn Book
5.2
K-3.
K-3
Keywords: Scotland -- Juvenile literature; Scotland; Scotland